Analysis of the influence of the human development index (HDI), unemployment and minimum wages on poverty during 2004-2022 - Sherly Ferdinandus; Hendri Dony Hahury; Hermi Oppier; Erlinda Erlinda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Poverty remains a major, multidimensional and complex issue that impedes the government’s efforts to boost regional economic growth. This condition is further complicated by the islands’ geographical conditions, which are severely limited in terms of access to education, and transportation. This study examines the impact of Human Development Index (HDI), unemployment rate, and minimum wage on the poverty rate in 11 districts / cities in Maluku Province. This study was conducted using a quantitative-descriptive method, utilizing secondary (time series) data obtained from the BPS Maluku Province during the period of 2004-2022. The data was examined using multiple linear regression analysis. The findings indicate that the Human Development Index (HDI) exerts a partial, positive, and statistically significant influence on the poverty rate, as evidenced by a regression coefficient of 1.886081 and a significance value of 0.0008. Meanwhile, unemployment exhibits no statistically significant impact on the poverty rate, as indicated by a coefficient of 0.011252 and a probability value of 0.9139 (> 0.05). Conversely, the regional minimum wage has been observed to exert a negative and significant influence on the poverty rate, as evidenced by a negative coefficient of -0.395722 and a probability value of 0.0000 (< 0.05). However, the simultaneous estimation of all independent variables indicates a substantial impact on the dependent variable. The implications of this research suggest the necessity for government policies that prioritize island development through the equitable distribution of infrastructure, including education, training, healthcare, and transportation. It is anticipated that this approach will contribute to the reduction of poverty and the enhancement of welfare across the Maluku Province as islands.